HUBUNGAN ANTARA POWER DAN FLEXIBILIY OTOT TUNGKAI TERHADAP HASIL SMASH KEDENG SEPAK TAKRAW DI SMA - Rahaji, Jiji; G. Simanjuntak, Victor; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe researcher's problem is: at the time of extracurricular activities sepak takraw in SMAN 9 Pontianak found that the students were difficult to determine timming properly when doing smash kedeng, the jump was not maximal and the movement was still rigid, it could be seen when the students got difficulties to do smash kedeng, so the ball was concerned on the net. The purpose of this correlation research is: to determine whether there is a relationship between power and flexibility of leg muscles to the results of smash kedeng and how big the contribution of eachvariable. This research is quantitative descriptive research with correlation research method, there were three variables investigated, those were the power, the flexibility leg muscle and the results of smash kedeng. This correlation research was done by correlation of bivariate and linear regression. The result of research relation of power, flexibility of leg muscle to result of smash kedeng. The results are: (1) there was a power relationship to the results of smash kedeng rcount 0.885 > rtable 0.482 with a contribution of 78.3%. (2) there was correlation of flexibility of leg muscle to result of smash kedengÂ  rcount 0,836 > rtable 0,482 with contribution 69,9%. (3) there was correlation between power and flexibility of leg muscle to result of smash kedeng rcount 0,708 > rtable 0,482 with contribution 87,1%. There was significant relation of three variables equal to 0,708 with contribution equal to 87,1%.Â Keywords: Power, Flexibility of leg muscle, The results of smash kedeng